2021
DOI: 10.1186/s12991-021-00377-9
|View full text |Cite
|
Sign up to set email alerts
|

A case of catatonia in the aftermath of the COVID-19 pandemic: does autism spectrum matter?

Abstract: Background There is growing concern about the psychopathological consequences of the COVID-19 pandemic. The prolonged stress due to the spreading fear of the contagion and to the enforced containment measures are deemed to trigger recurrences of preexisting mental disorders as well as the onset of new ones. From such perspective, clinical cases may be of primary ground to identify individual features and pandemic-related factors predisposing to the development of serious psychiatric symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…1 Such subthreshold autism spectrum, although unrecognized, could increase the risk of catatonia. 14 Since it is believed that the autistic dimension is not only present in individuals with ASD, but also widespread in the general population as a broader autistic phenotype or autistic traits [1], we might speculate that catatonia might be related to this autistic dimension even when not clinically evident and, as discussed in recent work, especially in patients with a history of traumatic events [14]. Beyond the recurrent speculations regarding the conceptualization of autism as an early form of catatonia, 9 some studies conducted on a validated animal model of autism have shown the beneficial effect of pharmacologically induced seizures and electroconvulsive therapy, one of the most effective treatments available for catatonia, in reducing autism-like behaviors in mice [15].…”
Section: Introductionmentioning
confidence: 99%
“…1 Such subthreshold autism spectrum, although unrecognized, could increase the risk of catatonia. 14 Since it is believed that the autistic dimension is not only present in individuals with ASD, but also widespread in the general population as a broader autistic phenotype or autistic traits [1], we might speculate that catatonia might be related to this autistic dimension even when not clinically evident and, as discussed in recent work, especially in patients with a history of traumatic events [14]. Beyond the recurrent speculations regarding the conceptualization of autism as an early form of catatonia, 9 some studies conducted on a validated animal model of autism have shown the beneficial effect of pharmacologically induced seizures and electroconvulsive therapy, one of the most effective treatments available for catatonia, in reducing autism-like behaviors in mice [15].…”
Section: Introductionmentioning
confidence: 99%